The multifaceted nature of interaction in higher education: Reflections from a genre-based approach. - Guinda, Carmen Sancho (Journal of Multilingual Theories & Practices, 2023)
What do we understand by 'communicative interaction' in university settings? Most often, our approach is somewhat reductionist as we tend to envisage interactions confined to class time and particularly to the traditional teacher-led lecture. This article aims to provide a genre-based overview of the diverse communicative interactions that take place in higher education, of the actors and variables shaping them, and of the multiple areas for study and improvement that derive from such analysis. The insights it offers pursue fostering reflective teaching by helping lecturers and syllabus planners to respectively gain awareness and examine their communicative practices and the learning models proposed, which may emphasize certain transversal soft skills over others. The outcome of this study may open up fresh avenues of research within the frames of English medium instruction (EMI) and languages for specific purposes (LSP).